THE ANALYSIS OF METACOGNITIVE AWARENESS AND POST LISTENING FEEDBACK ON EFL LISTENING ACTIVITIES - Dodi Mulyadi (Tarbawi : Jurnal Pendidikan Islam, 2016)
ABSTRACTListening is a critical component of effective communication and commonly regarded as the difficult skill by foreign language learners. Mostly, they find it difficult in understanding listening materials. They are still unable to comprehend or to understand the spoken words or phrases in the English. Thus, there are many factors affecting listening ability in mastering language. Metacognitive Awareness and Post Listening Feedback are used to find out the factors relating to students?? strategy use and their obstacles that they have experienced in comprehending spoken language. The research was designed quantitatively. The instruments for collecting data were Metacognitive Awareness Listening Questionnaire (MALQ) and a questionnaire of post listening feedback sheet. Participants of the study were fourteen English Education students at Univesitas Muhammadiyah Semarang in academic year 2015/2016. The findings indicated that the difficulties confronted by the learners are recognizing sounds, recognizing words, guessing word meaning, recognizing grammar patterns, working out what the speaker??s means. In addition, the reliability coefficient of MALQ calculated in this study was 0.79 with students?? metacognitve awareness comprising Problem solving with 4.4, Planning and evaluation with 3.70, Directed attention with 3.70, Directed attention with 3.0, Person knowledge with 2.60.  It can be concluded that the results can simply help instructors to find out the appropriate strategies and draw their attention to various information from students?? difficulties to help their students increase their listening ability to comprehend spoken English. Keywords: Metacognitive Awareness, Post Listening Feedback, and EFL Listening Activities